Intraocular robotic interventional surgical system (IRISS): Mechanical design, evaluation, and master–slave manipulation - Wilson, Jason T.; Gerber, Matthew J.; Prince, Stephen W.; Chen, Cheng‐Wei; Schwartz, Steven D.; Hubschman, Jean‐Pierre; Tsao, Tsu‐Chin (The international journal of medical robotics + computer assisted surgery, 2018)
Background: Since the advent of robotic‐assisted surgery, the value of using robotic systems to assist in surgical procedures has been repeatedly demonstrated. However, existing technologies are unable to perform complete, multi‐step procedures from start to finish. Many intraocular surgical steps continue to be manually performed. Methods: An intraocular robotic interventional surgical system (IRISS) capable of performing various intraocular surgical procedures was designed, fabricated, and evaluated. Methods were developed to evaluate the performance of the remote centers of motion (RCMs) using a stereo‐camera setup and to assess the accuracy and precision of positioning the tool tip using an optical coherence tomography (OCT) system. Results: The IRISS can simultaneously manipulate multiple surgical instruments, change between mounted tools using an onboard tool‐change mechanism, and visualize the otherwise invisible RCMs to facilitate alignment of the RCM to the surgical incision. The accuracy of positioning the tool tip was measured to be 0.205±0.003 mm. The IRISS was evaluated by trained surgeons in a remote surgical theatre using post‐mortem pig eyes and shown to be effective in completing many key steps in a variety of intraocular surgical procedures as well as being capable of performing an entire cataract extraction from start to finish. Conclusions: The IRISS represents a necessary step towards fully automated intraocular surgery and demonstrated accurate and precise master‐slave manipulation for cataract removal and—through visual feedback—retinal vein cannulation.